2006
DOI: 10.1038/sj.ijo.0803204
|View full text |Cite
|
Sign up to set email alerts
|

A population-based study investigating the association between metabolic syndrome and Hepatitis B/C infection (Keelung Community-based Integrated Screening Study No. 10)

Abstract: Objectives: We aimed to assess the association between metabolic syndrome (MS) and hepatitis B/C virus infection using a large population-based study. Design and methods: A population-based cross-sectional study design was adopted with a total of 53 528 subjects being enrolled from the integrated multiple diseases screening program in Keelung, Taiwan. Evidence of past hepatitis B/C infection, acquired during childhood or as a young adult, was identified during the two-stage liver cancer screening part of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
110
4
2

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(142 citation statements)
references
References 25 publications
24
110
4
2
Order By: Relevance
“…In this study, we consistently showed HCV infection was associated with a lower TG level [18]. In the transgenic mouse model, HCV core protein appears to interfere with the hepatic assembly and secretion of ApoB containing very low-density lipoproteins (VLDL) [41].…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…In this study, we consistently showed HCV infection was associated with a lower TG level [18]. In the transgenic mouse model, HCV core protein appears to interfere with the hepatic assembly and secretion of ApoB containing very low-density lipoproteins (VLDL) [41].…”
Section: Discussionmentioning
confidence: 71%
“…Recently, a population-based study revealed a positive association between HCV infection and hyperglycemia [18], but the association disappeared when adjusted for age and gender. However, our analyses demonstrated that more chronic hepatitis C patients had an impaired fasting glucose compared to sex-and age-matched controls (data not shown).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Jan et al 19 have found that, after adjusting for age and gender, those who are HBsAg( þ ) have lower risk (OR ¼ 0.84, Po0.05) for concomitant metabolic syndrome than those who are HBsAg(À). In that study, the criterion to define metabolic syndrome is different and some potential confounders such as BMI and smoking are not adequately adjusted.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the relationship between the status of hepatitis B immunity and metabolic syndrome remains unclear although chronic hepatitis B infection has been reported to associate with metabolic syndrome. 19 In Taiwan, the universal hepatitis B vaccination program has been initiated for children since 1986. Thus, the goal of our cross-sectional study is to assess the prevalence of overweight, obesity and metabolic syndrome in a cohort of university freshmen in Taiwan.…”
Section: Introductionmentioning
confidence: 99%